A Plea for Embodied Spirituality: The Role of the Body in Religion By F. Watts (2021) : Reviewed by Rebekah Wallace - Wallace, Rebekah (Body and religion, 2021)
A Plea for Embodied Spirituality: The Role of the Body in Religion By F. Watts (2021) London: SCM Press, ix + 230pp.